A COMPARISON OF THREE DIFFERENT TECHNIQUES TO PERFORM BI-DIRECTIONAL GLENN SHUNT - Hussain, Syed Aqeel; Ahmed, Iftikhar; Haq, Rana Intesar Ul; Saleem, Kamal (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare three surgical techniques utilized to perform Bi-directional Glenn Shunt.Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was carried out from January 2011 to September 2013 at the Armed Forces Institute of Cardiology / National Institute of Heart Diseases, Rawalpindi, Pakistan.Material and Methods: Patients were divided in three groups which: Cardio-Pulmonary Bypass group (Group I), Local veno-atrial by-pass group (Group II) and Clamp & sew group (Group III). Clinical outcome of the three surgical techniques was compared in terms of mean post-operative bleeding (ml), duration of vaso-active support (hours), duration of post-operative ventilation and ICU stay (hours).Results: Mean postoperative bleeding in group III was lesser than other two groups (45 ± 15ml vs 70 ± 25 ml and 68±25 ml in group I and II, respectively). Patients in group III needed inotropic support for fewer hours (23.88±4.23 hours) as compared with group I and II (34 ± 9 and 32 ± 11 hours). Similarly, patients in group III had shorter duration of ventilatory support (6.5 ± 3.5 vs 15 ± 9 and 12 ± 6 hours). The ICU length of stay was26 ± 11 hours in group I patients compared to 36 ± 12 hours in group I and 35 ± 9 hours in group II patients.Conclusion: Clinical outcome of Bi-Directional Glenn shunt with clamp & sew technique is better as compared with the shunt performed with cardiopulmonary bypass or local veno-atrial bypass technique.